2016
DOI: 10.3390/ijms17121987
|View full text |Cite
|
Sign up to set email alerts
|

Tools for Sequence-Based miRNA Target Prediction: What to Choose?

Abstract: MicroRNAs (miRNAs) are defined as small non-coding RNAs ~22 nt in length. They regulate gene expression at a post-transcriptional level through complementary base pairing with the target mRNA, leading to mRNA degradation and therefore blocking translation. In the last decade, the dysfunction of miRNAs has been related to the development and progression of many diseases. Currently, researchers need a method to identify precisely the miRNA targets, prior to applying experimental approaches that allow a better fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
232
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 346 publications
(247 citation statements)
references
References 104 publications
2
232
0
5
Order By: Relevance
“…It is clear that circRNAs could sequester miRNAs to control the expression level of the target genes. Hence, Bioinformatic prediction (DIANA, Vlachos & Hatzigeorgiou, , http://diana.imis.athena-innovation.gr/DianaTools/index.php; Targetscan, Riffo‐Campos, Riquelme, & Brebi‐Mieville, , http://www.targetscan.org/vert_71/; and miRDB, Wong & Wang, , http://www.mirdb.org/miRDB/) was applied to look for the probable target genes of miR‐488‐3p. Results showed that DCX was closely related with the miR‐488‐3p in all databases.…”
Section: Resultsmentioning
confidence: 99%
“…It is clear that circRNAs could sequester miRNAs to control the expression level of the target genes. Hence, Bioinformatic prediction (DIANA, Vlachos & Hatzigeorgiou, , http://diana.imis.athena-innovation.gr/DianaTools/index.php; Targetscan, Riffo‐Campos, Riquelme, & Brebi‐Mieville, , http://www.targetscan.org/vert_71/; and miRDB, Wong & Wang, , http://www.mirdb.org/miRDB/) was applied to look for the probable target genes of miR‐488‐3p. Results showed that DCX was closely related with the miR‐488‐3p in all databases.…”
Section: Resultsmentioning
confidence: 99%
“…The potential binding sites of miR‐219a‐5p and circCDR1as or SOX5 were predicted by starBase (http://starbase.sysu.edu.cn/index.php) or TargetScan (http://www.targetscan.org/vert_72/). The use and parameters of starBase and TargetScan were shown as previous reports . The psiCHECK‐2 dual‐luciferase vectors (Promega, Madison, WI, USA) were used to generate the wild‐type luciferase reporter vectors (circCDR1as‐WT and SOX5‐WT) and corresponding mutant (circCDR1as‐MUT and SOX5‐MUT) by cloning the sequences of circCDR1as or 3′ untranslated regions (UTR) of SOX5 containing miR‐219a‐5p binding sites.…”
Section: Methodsmentioning
confidence: 99%
“…The high false‐positive rates of target predictions are the major limitations associated with most of the prediction software. Therefore, only those targets were selected, which had an intersection with at least two major algorithms (Figure ) . The total 139 974 genes were predicted by using target prediction tools and 259 genes were selected out of the total predicted genes for further analysis based on the following criteria: (a) role of genes during virus infection; (b) presence of the gene in at least two databases; and (c) significant scores of the target genes (Table S2).…”
Section: Resultsmentioning
confidence: 99%